Safer-sex discussions in polyamorous relationships: Qualitatively investigating sexual scripts, relational and health implications. - Chatterjee, Karishma; Cummins, Molly Wiant; Brannon, Grace Ellen (Journal of Social & Personal Relationships, 2026)
Sexual communication is integral for many interpersonal relationships' success, with both relational and individual health affected by the quality of sexual communication between partners. In polyamorous relationships, partners make agreements regarding their engagement in concurrent romantic and/or sexual relationships. The objective of this project was to examine how safer-sex practices are discussed within polyamorous relationships through the lens of sexual scripts theory. Participants (n = 26) were individuals self-identifying as polyamorous who reported their discussions of safer-sex practices, as well as their relational and health implications resulting from such conversations. The prevailing cultural script of having discussions about safer-sex practices, which participants learned from other poly community members and partners, was key to successfully establishing multiple intimate relationships. Interpsychic scripts were illustrated in participants' desire to have recurrent open and honest discussions, including when a potential new partner was coming into the picture. Interpersonal scripts were seen in the topics of these discussions participants reported having, which included using condoms, sharing sexually transmitted infection (STI) results, understanding risk tolerance, and knowledge of other partners and their sexual practices. Having these discussions successfully not only allowed participants to pursue new sexual relationships but also helped build relational trust and intimacy. Refusal by potential partners to discuss safer-sex practices was perceived as a red flag and resulted in either cooling off relational interest or avoiding sexual activity. This study's findings suggest health and relational implications for individuals in polyamorous relationships. Healthcare practitioners and relationship counselors should offer STI testing to all individuals regardless of marital status, allowing for destigmatization of STI testing.